Efficient distributed algorithms for self testing of multiple processor systems - Hosseini, S.H.; Jamal, N. (IEEE transactions on computers, 1992)
Multiple processor systems allow both highly reliable and highly fast service. Distributed self-test algorithms that attempt to improve both the reliability and the performance of these systems are proposed. In these algorithms, reliability is improved by considering the distributed mode of control and assigning processors to test each other periodically for the diagnosis and isolation of the faulty processors and interprocessor links. Meanwhile, performance is improved by considering a dynamic testing strategy and minimizing testing overhead by reducing the number of tests performed on each processor. Simulation results show the effectiveness of the algorithms.< >